Interrogative Sentences Between East Manggarai Language And English - Febriansi Novari Rana; Dahlia D. Moelier; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This research aims to describe the structure of interrogative sentences between East Manggarai Language And English also to find the contrast of interrogative sentences  between East Manggarai Language And English.This research is a descriptive qualitative research with the sample of native speakers of East Manggarai language in Satar Punda Village, East Manggarai language, NTT. The method used is contrastive method purposed by Tarigan and using sentence function theory from Hariyono & Rahman for analyzed the Interrogative sentence in the form of Yes/No question. Then used the theory purposed by Azar to find the sentence function and the sentence pattern in the form of Wh-Question and also Question Tag.The results of this research indicated that there was a dominant difference in language use between East Manggarai and English, namely in terms of sentence structure where the placement of the interrogative words used has a very significant difference. One of the data found in the interrogative sentence in East Manggarai language is a Yes/No Question sentence, which generally has a predicate and also subject at the beginning of the sentence and ends with the Question word (koh, teh, teh gah, neh, etc). Meanwhile, in English the interrogative sentences structure is generally preceded by a Question word (Am, Is, Are, and Do, Does, Did, etc). In addition, the verb in the East Manggarai language also can not undergo changes and get modification because they were not influenced by adverbs. While, the verb in English can undergo changes depending on the word convention and also the context in the sentence.